Before American History Nationalist Mythmaking and Indigenous Dispossession - Mucher, Christen (Writing the Early Americas, 2022)
Before American History juxtaposes Mexico City's famous carved Sun Stone with the mounded earthworks found throughout the Midwestern states of the U.S. to examine the project of settler nationalism from the 1780s to the 1840s in two North American republics usually studied separately. As the U.S. and Mexico transformed from European colonies into independent nations-and before war scarred them both-antiquarians and historians compiled and interpreted archives meant to document America's Indigenous pasts. These settler-colonial understandings of North America's past deliberately misappropriated Indigenous histories and repurposed them and their material objects as "American antiquities," thereby writing Indigenous pasts out of U.S. and Mexican national histories and national lands and erasing and denigrating Native peoples living in both nascent republics.Christen Mucher creatively recovers the Sun Stone and mounded earthworks as archives of nationalist power and Indigenous dispossession as well as objects that are, at their material base, produced by Indigenous people but settler controlled and settler interpreted. Her approach renders visible the foundational methodologies, materials, and mythologies that created an American history out of and on top of Indigenous worlds and facilitated Native dispossession continent-wide. By writing Indigenous actors out of national histories, Mexican and U.S. elites also wrote them out of their lands, a legacy of erasure and removal that continues when we repeat these eighteenth- and nineteenth-century settler narratives and that reverberates in discussions of immigration, migration, and Nativism today.